Dicamba-based preemergence herbicide tank mixtures improved residual weed control in dicamba-resistant soybean - Dhanda, Sachin; Singh, Navjot; Ikley, Joseph T.; DeWerff, Ryan P.; Werle, Rodrigo; Sarangi, Debalin (Frontiers in Agronomy, 2025)
In February 2024, the United States Environmental Protection Agency (EPA) vacated the registrations of dicamba products for over-the-top applications on dicamba-resistant cotton and soybean following a court ruling. This decision has raised significant concerns among United States farmers, who now have limited chemical options to manage tough-to-control weeds. However, the risk of off-target dicamba movement to sensitive plants remains a critical issue. If permitted in the future, applying dicamba as a preemergence (PRE) treatment, tank-mixed with other soil residual herbicides, could help reduce off-target movement while preserving its utility for managing problem weeds. Field experiments were conducted in 2022 and 2023 in Minnesota and North Dakota, and in 2021 and 2022 in Wisconsin, to evaluate the effectiveness of dicamba-based PRE herbicide mixtures in soybean. Across all site-years, dicamba tank mixed with other soil residual herbicides provided better control of targeted weed species at 21 d after treatment (DAT) compared to applying the residual herbicides alone. In Minnesota, dicamba-based herbicide tank mixes provided an average waterhemp control of 72%, compared to 59% for treatments without dicamba at 21 DAT. Similarly, in North Dakota, waterhemp control at 21 DAT improved from 74% with residual herbicides alone to 97% when tank mixed with dicamba. In Wisconsin, dicamba-based tank mixes resulted in 96% control of common ragweed and 83% of velvetleaf, versus 83% and 73% for those species, respectively, without dicamba. At the Minnesota site, adding dicamba to residual herbicides improved common lambsquarters and giant ragweed control by 17% and 20%, respectively, and their densities were reduced by at least 50%. At the North Dakota site, kochia control was improved by 23% with dicamba PRE. The results from this research outlined the effectiveness of PRE application of dicamba tank mixed with other residual herbicides for effective weed management in the Upper Midwest.